The early achievement of measurable residual disease negativity in the treatment of adults with Philadelphia‐negative B‐cell acute lymphoblastic leukemia is a strong predictor for survival. Issue 2 (19th November 2019) - Yilmaz, Musa; Kantarjian, Hagop; Wang, Xuemei; Khoury, Joseph D.; Ravandi, Farhad; Jorgensen, Jeffrey; Short, Nicholas J.; Loghavi, Sanam; Cortes, Jorge; Garcia‐Manero, Guillermo; Kadia, Tapan; Sasaki, Koji; et al.
Abstract: The minimal or measurable residual disease (MRD) status following induction/consolidation chemotherapy is an important prognostic endpoint in adult patients with newly diagnosed acute lymphoblastic leukemia (ALL). However, the optimal time‐point (TP) of MRD assessment and its impact on outcome remains unclear. We analyzed 215 patients with newly diagnosed Philadelphia negative B‐cell ALL who received intensive chemotherapy, and had available MRD assessment by multicolor flow cytometry at two separate TPs. The median time to first TP (1TP) and second TP (2TP) were 24 and 110 days, respectively. At 1TP, 148 patients (68%) were MRD negative and 67 (32%) were positive. Of the 148 patients with negative MRD at 1TP, 147 (99%) maintained it through 2TP. Patients who were MRD negative at both TPs, early MRD responders, had the 3‐year event‐free survival (EFS), and overall survival (OS) rates of 65% and 76%, respectively. Patients with improved MRD status from positive to negative, late MRD responders, had lower 3‐year EFS and OS rates, 42% and 58%, respectively ( P = .001). Multivariate analysis showed that KMT2A ( MLL ) rearrangement and MRD positivity at 1TP were the only factors correlated with worse OS. In conclusion, the earlier achievement of MRD negative remission is a stronger prognostic factor for survival.